Proceedings of the First International Workshop on the Analysis of Multi-temporal Remote Sensing Images : (World Scientific, 2002)
Proceedings of the First Intl Workshop on Multitemp 2002, held at the University of Trento, Italy, September 13-14, 2001. Brings together the methodological aspects of multi-temporal remote sensing image analysis, real applications and end-user requirements